2020
DOI: 10.21203/rs.3.rs-29627/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of tumor cell senescence in non-professional phagocytosis and cell-in-cell structure formation

Abstract: Background: Non-professional phagocytosis is usually triggered by stimuli such as necrotic cell death. In tumor therapy, the tumors often disappear slowly and only long time after the end of therapy. Here, tumor therapy inactivates the cells by inducing senescence. Therefore, study focused whether senescence is a stimulus for non-professional phagocytosis or whether senescent cells themselves phagocytize non-professionally.Results: Senescence was induced in cell lines by camptothecin and a phagocytosis assay w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…This feature was first reported over a century ago (7)(8)(9), when little was known about its composition, mechanism of biogenesis or the implications of its existence. Subsequently, studies have shown that CIC events are easily identifiable through hematoxylin-eosin staining and are common events in malignancies (10,11), such as lung cancer (12), breast cancer (13,14), melanoma (15,16), and adenocarcinoma (17,18), also having been detected in benign tumors (19).…”
Section: Cell-in-cell Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature was first reported over a century ago (7)(8)(9), when little was known about its composition, mechanism of biogenesis or the implications of its existence. Subsequently, studies have shown that CIC events are easily identifiable through hematoxylin-eosin staining and are common events in malignancies (10,11), such as lung cancer (12), breast cancer (13,14), melanoma (15,16), and adenocarcinoma (17,18), also having been detected in benign tumors (19).…”
Section: Cell-in-cell Structuresmentioning
confidence: 99%
“…CIC-related tumor dormancy and cellular senescence may also work as an escape mechanism against chemotherapy and other toxic agents. Threatened cells are sheltered from harm within other cells, and dormant cells are also more resistant against harmful agents and treatment drugs (14,66), meaning that CIC structure-related senescence may be linked to worse prognosis (18).…”
Section: Cannibalismmentioning
confidence: 99%